Stability of oil-in-water (O/W) emulsions with chia (Salvia hispanica L.) mucilage. (December 2016) - Capitani, Marianela I.; Nolasco, Susana M.; Tomás, Mabel C.
Abstract: The stability of oil-in-water (O/W) emulsions prepared with different concentrations of chia mucilage extracted by two different methods was evaluated as a function of refrigerated storage time. O/W emulsions (20:80 wt/wt) formulated with refined corn oil, chia mucilage dispersions (0.25, 0.50, 0.75 and 1.00% wt/wt) and 0.1% wt/wt of Tween 80 were stored at 4 ± 1 °C for 120 days, evaluating their stability periodically. An emulsion without added mucilage was also prepared as a control. The emulsions were characterized determining the flow behavior, the evolution of the backscattering profiles (%BS), particle size distribution, and microscopic observations. Viscosity increased as increasing mucilage concentration, revealing a pseudoplastic flow behavior. The most stable emulsions during storage were those with ≥0.75% chia mucilage concentration, and those with mucilage obtained by Method II (which presents a higher level of purity than MI mucilage). All the emulsions prepared with mucilage obtained by Method II presented smaller droplet diameters ([D4, 3]) than those prepared with mucilage obtained by Method I. Particle size distribution did not show important variations as a function of time, concentration and type of mucilage, presenting in general a unimodal behavior. The results suggested that the addition of chia mucilage (≥0.75%) to O/W emulsions improved their stability against gravitational phase separation by increasing the viscosity of the aqueous phase, limiting the mobility of the oil droplets in the emulsions. Graphical abstract: Highlights: Emulsions stabilized by different levels of chia mucilage obtained by different methods were examined. The viscosity of emulsions was higher with increasing mucilage concentration. All the emulsions exhibited a pseudoplastic flow behavior. Stability of emulsions was affected by the extraction methods of chia mucilage. Emulsions formulated with ≥0.75% chia mucilage were more stable.